A comparative investigation on phenolic composition, antioxidant and antimicrobial potentials of Salvia heldreichiana Boiss. ex Bentham extracts - Bardakci, H.; Celep, E.; Gozet, T.; Kurt-Celep, I.; Deniz, I.; Sen-Utsukarci, B.; Akaydin, G. (ELSEVIER, 2019)
The purpose of the present work is to screen phenolic composition and evaluate the antioxidant and antimicrobial activities of the main extract and subextracts of Salvia heldreichiana, an endemic plant from Turkey. The aerial parts have been powdered and extracted with MeOH initially and then partitioned with chloroform (CHCl3), ethyl acetate (EtOAc) for the generation of subextracts along with the remaining water (R-H2O). Total phenolic, phenolic acid, flavonoid and proanthocyanidin contents present in the MeOH, CHCl3, EtOAc and R-H2O extracts were measured. Presence of 22 phenolic metabolites were confirmed by utilizing LC-MS/MS in MRM scan mode and then Rosmarinic acid (RA) contents of each extract were quantified by HPTLC-densitometry, since the biological effects of many medicinal plants, including Salvia sp. is attributed to RA content. Antioxidant capacities of the aforementioned extracts were estimated using several procedures including free radical scavenging and metal-associated activity and then disc diffusion method was employed to designate their antibacterial and antifungal activities. The results obtained from the current study has revealed a positive correlation between the phenolic composition and the antioxidant profile as well as the antimicrobial activities of the extracts. Among the tested extracts, EtOAc subextract showed the highest antioxidant and antimicrobial activities consistent with the highest phenolic and RA content. (C) 2019 SAAB. Published by Elsevier B.V. All rights reserved.
Keywords: Salvia heldreichiana; Antioxidant; Antimicrobial; LC-MS/MS; HPTLC; Rosmarinic acid